Inclusive Education in Azerbaijan : A role of assistive technologies in facilitating its effectiveness - Beydullayeva, Aysel (ADA University, 2022)
This study used a qualitative research methodology to explore the role of assistive technologies employed by inclusive classroom teachers in two public schools in Baku. In addition, it studied the perceptions research participants had and practices used by teachers and parents to educate children with special educational needs. Semi-structured interviews with two principals, six classroom teachers, and four parents confirm that inclusive classroom teachers utilize assistive technologies. Yet, the range of assistive technologies used by the two schools differed significantly. In addition, all participants agreed that assistive devices play an essential role in implementing inclusive education. Regarding practices, research participants agreed that it is required to implement inclusive education. This practice has social and emotional benefits for students with special educational needs and allows them to achieve effective learning. Overall, the study provides readers with comprehensive information about assistive devices and their role in the facilitation of inclusive schooling in the Azerbaijani context.
Keywords: Inclusive education.; Inclusive education -- Azerbaijan; Teaching strategies -- Inclusive education.; Education